2019
DOI: 10.3389/fpubh.2019.00311
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Frontolimbic Connectivity and Mood Symptoms in Young Adult Cannabis Users

Abstract: Objective: The endocannbinoid system and cannabis exposure has been implicated in emotional processing. The current study examined whether regular cannabis users demonstrated abnormal intrinsic (a.k.a. resting state) frontolimbic connectivity compared to non-users. A secondary aim examined the relationship between cannabis group connectivity differences and self-reported mood and affect symptoms.Method: Participants included 79 cannabis-using and 80 non-using control emerging adults (ages of 18–30), balanced f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 183 publications
(155 reference statements)
0
18
0
Order By: Relevance
“…Cannabis is one of the most used substances worldwide (8). After alcohol and tobacco, cannabis ranks first for used substances in the United States (US) (9,10) and Canada (11).…”
Section: Prevalence Of Cannabis Usementioning
confidence: 99%
See 3 more Smart Citations
“…Cannabis is one of the most used substances worldwide (8). After alcohol and tobacco, cannabis ranks first for used substances in the United States (US) (9,10) and Canada (11).…”
Section: Prevalence Of Cannabis Usementioning
confidence: 99%
“…The endogenous cannabinoid (or endocannabinoids) system (ECS) ( 29) is involved in regulating functions such as mood, cognition, feeding behavior, pain perception, inflammation, and stress responses (8,30). Furthermore, there is evidence that a hypoactive ECS may contribute to depression in humans (6).…”
Section: Potential Mechanisms Underlying the Relationship Between Cannabis And Depressionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, resting-state functional connectivity (rsFC) analyses can enhance understanding of specific brain networks and organization, particularly relating to the amygdala. A small number of studies have examined rsFC in CUD (Pujol et al, 2014; Shollenbarger et al, 2019; Whitfield-Gabrieli et al, 2018), but two of the three studies focused on the default-mode network (DMN) (Pujol et al, 2014; Whitfield-Gabrieli et al, 2018). One of these studies showed that long-term cannabis users have increased DMN connectivity with certain subregions of the PCC, along with decreased connectivity with other subregions compared to controls (Pujol et al, 2014).…”
Section: Introductionmentioning
confidence: 99%